INSTALASI PERMESINAN PADA KAPAL PSP 01 - Anjaya Purwa Wiyastra; Mulyono S. Baskoro; Fis Purwangka (Fakultas Perikanan dan Ilmu Kelautan, 2012)
PSP 01 boat is an accustomed boat and also fishing vessels that owned by the Department of Fisheries Resource Utilization (PSP), Faculty of Fisheries and Marine Sciences (FPIK), IPB. These ships use an inboard propulsion four stroke diesel engine from Mitsubishi Canter truck with type 4D30-C. This study aims to describe the modifications to the installation of ship machinery at the PSP 01 boat and describe the suitability of its machinery installation guidelines refer to the FAO in 2009 on the Safety Guide for Small Fishing Boats. These study approach by using case study method in which observation and data collection that includes modifications to the installation of ship machinery PSP 01 and compliance with the FAO guidelines on Safety Guide for Small Fishing Boats. The results obtained that the PSP 01 engine already modified on the ignition system, fuel system, lubrication system, transmission system, and engine cooling system. Based on FAO guidelines in 2009 on the Safety Guide for Small Fishing boats, installation of machinery on PSP 01 boat in bilge pump fullfilled 58.33%, fuel system fulfilled 52.63%, the combustion gas exhaust system met 33.33%, the engine room vents are met 0%, range 85.71% met the electrical installation, battery installation are met 100%, daily checks before turning on the engine are met 75%, daily checks after turning on the engine are met 100%, the examination of every fourteen days are met 20%, and the examination of every 100 -150 hours of engine operation are fulfilled 0%. Based on FAO guidelines in 2009 on the Safety Guide for Small Fishing Boats, installation of Machinery on PSP 01 Boat on a whole scale are fulfilled 47,65%.